Regulation of the Legal Status of Executive Personnel in Ensuring the Economic Security of a Company - Pylypenko, O. І. (Statistics of Ukraine, 2021)
The effective company operation involves significant scopes of economic information, which requires improvements in the management related with the economic security aspect. The present-day conditions determine new requirements pertaining to the security of accounting data, which are, in particular, focused on taking measures to prevent their unauthorized use. The study is devoted to the elaboration of recommendations on the regulation of the legal status of executive personnel dealing with accounting data, in order to create a mechanism preventing unauthorized uses of data and helping improve operation of the economic security system at company level. In the current market environment, company managers face new challenges related with search and utilization of competitive advantages, which raises the company management’s concern with the protection of economic data from threats of the internal and external origin. Using of computer systems for accounting as a factor for the effective company operation raises the importance of solutions to problems related with data protection and limitation of data access. This calls for the higher responsibility of the accounting personnel, which has to be regulated and shown in internal economic documents, which is supposed to minimize the threat and simplify the activities of the company unit responsible for economic security. The job duties and rights of the chief accountant and the head of the department for internal control (audit), related with economic security, are outlined. These duties and rights are proposed to include in the company regulations on economic security and to the job descriptions, which is supposed to decrease the occurrences of fraud and manipulations on the part of company employees. The efficiency of job descriptions presented in the article is ensured by the inclusion of the item on the mode of access to the commercial secret of a company in the regulations on economic security; this item contains standard requirements to preparation, use, storage, communication and protection of information. The elaboration of organizational documents together with job descriptions specifying the duties of staff involved in the management of economic security of a company will enable to launch a highly performing system for the economic security at company level.